Parametric Study of Magnetosheath Jets in 2D Local Hybrid Simulations - Tinoco-Arenas, Arturo; Kajdič, Primož; Preisser, Luis; Blanco-Cano, Xóchitl; Trotta, Domenico; Burgess, David (Frontiers in Astronomy and Space Sciences, 2022)
We perform 2D local hybrid simulations of collisionless shocks in order to study the properties of simulated magnetosheath jets as a function of shock properties, namely their Alfvénic Mach number (MA) and geometry (angle between the upstream magnetic field and the shock normal, θBN). In total we perform 15 simulations with inflow speeds of Vin = 3.3 CA (Alfvén velocity), 4.5 CA and 5.5 CA and θBN = 15°, 30°, 45°, 50°, and 65°. Under these conditions, the shock MA varied between 4.28 and 7.42. In order to identify magnetosheath jets in the simulation outputs, we use four different criteria, equivalent to those utilized to identify subsets of magnetosheath jets, called high-speed jets (Plaschke and Hietala and Angelopoulos, Ann. Geophys., 2013, 31, 1877–1889), transient flux enhancements (Němeček et al., Geophys. Res. Lett., 1998, 25, 1273–1276), density plasmoids (Karlsson et al., J. Geophys. Res., 2012, 117, a–n; Karlsson et al., J. Geophys. Res., 2015, 120, 7390–7403) and high-speed plasmoids (Gunell et al., Ann. Geophys., 2014, 32, 991–1009). In our simulations, the density plasmoids were produced only by shocks with MA ≥5.7, while the high-speed plasmoids only formed downstream of shocks with MA ≥6.97. We show that higher MA shocks tend to produce faster jets that tend to have larger surface area, mass, linear momentum and kinetic energy, while these quantities tend to be anticorrelated with θBN. In general, the increase of θBN to up to 45° results in increased jet formation rates. In the case of high-speed jets in runs with Vin = 3.3 CA and high-speed plasmoids, the jet formation anticorrelates with θBN. The jet production all but ceases for θBN = 65° regardless of the shock’s MA. The maximum distances of the magnetosheath jets from the shocks were ≲140 di (upstream ion intertial lengths), which, estimating 1 di ∼100–150 km at Earth, corresponds to 2.4–3.3 Earth radii. Thus, none of the simulated jets reached distances equivalent to the average extension of the Earth’s subsolar magnetosheath, which would make them the equivalents of geoeffective jets. Higher MA shocks are probably needed in order to produce such jets.